Pastoral Reflections on St. Augustine's Ordo Amoris - Goad, Keith (Perichoresis, 2025)
In this practical reflection on the Ordo Amoris as outlined by St. Augustine, I will endeavor to frame our understanding of genuine Christian love in contemporary pastoral and Christian context. By reflecting on the general theme of Augustine ordo as having interacting spheres whereby the Christian has shifting (but real) priorities towards God, self, and others, this reflection will highlight the necessity of covenant relational community as a critical component of our godly Image Bearing. To love others is to reflect God; to love God is to acknowledge his sovereignty. To be neglectful in our loves (regardless of which category we are neglecting) is to reject God and to deny his commandments to us.